Another Gaze 04. - Shreir, Daniella; Williams, Missouri; Makary, J.; da Costa, Cassie; Miller, Zara Joan (London : Another Gaze, 2020)
Gay, Amandine ; Anger, Zia ; Connor, Ashley ; Bromberg, Betzy ; Afro-Brazilian Roundtable ; Mazzetti, Lorenza ; Horn, Rebecca ; Sontag, Susan ; Akerman, Chantal ; Bausch, Pina ; Santiago Muñoz, Beatriz ; Anderson, Madeline ; De Hirsch, Storm ; LaBruce, Bruce ; Montezuma, Magdalena ; Li, Gong ; Brazilian Cinemas ; On Kira Muratova ; Anthropocenic Cinemas ; The Internet ; On Anne Charlotte Robertson ; Against Lists
boek